Impact of maternal self-efficacy and associated factors on maintaining exclusive breastfeeding in the city of Piracicaba-SP: Cohort study - Jucilene Casati Lodi; Clarice Santana Milagres; Priscila Alves Giovani; Luciane Miranda Guerra; Rosana de Fatima Possobon (O Mundo da Saúde, 2019)
A mother’s confidence in her ability to breastfeed can be studied within the construct of self-efficacy, in which the woman must believe that she is able to perform certain tasks or behaviors successfully to achieve desirable results. Thus, the objective of this study was to evaluate the level of self-efficacy in breastfeeding, both during the pregnancy and in the immediate puerperium, and the factors associated with the maintenance of exclusive breastfeeding in the first month. A cohort study was carried out with 210 women attended at the family health centers of the city of Piracicaba-SP. Two instruments were applied to assess self-efficacy. The first one, was during the pregnancy in the health unit together with the socioeconomic and demographic data, and the second in the immediate puerperium, via telephone, in addition to the obstetric data. The association between variables and maintaining breastfeeding exclusively until the 30th day of life was identified by the chi-square test and logistic regression analysis (p≤0.05). Half of the sample was aged ≥24 years, and 78.6% of the women reported that they were exclusively breastfeeding on the 30th day, and of these women 81.8% had the presence of their partner. The instrument applied during pregnancy was not significant with maintaining exclusive breastfeeding, but when applied during the immediate puerperium, women who had a medium and high level of self-efficacy were more likely to maintain exclusive breastfeeding. It was concluded that women's confidence level reflects their ability to breastfeed and can guide specific interventions for the promotion and maintenance of exclusive breastfeeding.